Answer:
The solution is B) (3, 1).
Explanation:
For the system of equations given, there are few different ways to solve. Since the second equation y = 2x - 5 is already solved for 'y', we can use substitution and place the expression '2x - 5' in for 'y' in the first equation and solve:
2x - 5 + 2 = x
We can also solve for 'y' in the first equation and then set the two equations equal to each other:
y + 2 - 2 = x -2 or y = x -2 so, 2x -5 = x - 2
Either way, when we solve for 'x', we get:
2x - 3 = x or -3 = -x, so x = 3
Plugging in the value of 'x' into the second equation:
y = 2(3) - 5 or y = 6 - 5 or y = 1
The ordered pair (x, y) would be (3, 1).